CAPITAL MANAGEMENT IN THE LIGHT OF FINANCIAL ENVIRONMENT RISKS-AN APPLIED STUDY IN A SAMPLE OF IRAQI BANKS (World Economics and Finance Bulletin, 2025)
The current research aims to analyze and evaluate capital management methods in Iraqi banks in light of the escalating financial risks facing the banking environment, such as liquidity risks, credit risks, and economic fluctuations, The research adopted a practical approach by collecting data from a representative sample of Iraqi banks using a quantitative analytical approach. Financial data from a group of Iraqi banks was collected and analyzed during 2022 and 2023, The research utilized advanced statistical analysis tools, particularly simple regression and analysis of variance (ANOVA), to examine the relationship between capital management and financial risks in the banking environment, A number of basic financial indicators were also employed to measure capital adequacy levels, such as the capital adequacy ratio (CAR), liquidity indicators, and asset quality, along with indicators reflecting the various levels of risk facing banks The research revealed a general weakness in capital management among the Iraqi banks in the research sample, particularly given the decline in the capital adequacy index during 2023 compared to 2022. This illustrates how these banks are more vulnerable to financial risks and are not adequately equipped to withstand shocks. The study's most significant recommendation is that Iraqi banks examine their capital management procedures, emphasizing the improvement of capital adequacy to handle any upcoming financial crises.